The Influence of Mental Imagery, User Interactivity, Visual Appeal, and Emotional Experience on the Intention to Visit Virtual Tourism - Naila Indah Syahaarani; Novel Idris Abas (Universitas Muhammadiyah Surakarta, 2025)
The research seeks to investigate the impact of User Interactivity, Visual Appeal, and Emotional Experience on intentions to visit sites related to Indonesian Cultural Virtual Tourism. It adopts a quantitative methodology, drawing on primary information collected through surveys administered via Google Forms. Data processing in this investigation employs the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach, facilitated by the Smart PLS 4.0 application. Outcomes from the analysis show that all elements in the proposed framework maintain favorable connections in line with the initial predictions. Notably, User Interactivity exerts a beneficial influence on Tourist Visit Intention, while Visual Appeal markedly shapes Emotional Experience. Furthermore, User Interactivity significantly contributes to Emotional Experience, Emotional Experience positively drives Tourist Visit Intention, and Visual Appeal also promotes a constructive effect on Tourist Visit Intention. These insights underscore the interconnected roles of these factors in enhancing virtual tourism engagement.